2011
DOI: 10.1530/eje-10-0703
|View full text |Cite
|
Sign up to set email alerts
|

Circulating levels of IGF1 are associated with muscle strength in middle-aged- and oldest-old women

Abstract: Objective: In aging populations, poor handgrip strength has been associated with physical disability and mortality. IGF1 is an important mediator of muscle growth and regeneration affecting muscle function. We studied the relationship between circulating levels of IGF1, its binding protein 3 (IGFBP3), and handgrip strength and physical performance in middle-aged-and oldest-old subjects. Design: Cross-sectional analysis in two different cohorts composed of middle-aged-(nZ672, mean 63.9G6.7 years) and oldest-old… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
32
0
2

Year Published

2013
2013
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(36 citation statements)
references
References 53 publications
(64 reference statements)
1
32
0
2
Order By: Relevance
“…Our results suggest that older women are more sensitive to muscle strength alterations throughout ageing, probably as a result of sex differences in muscle mass as well as hormonal factors [25, 26]. It seems to be particularly important for the weakest to enhance their levels of muscular strength and build up muscle mass early in life, where targeted preventative efforts may be launched, to reduce their risk of premature death.…”
Section: Discussionmentioning
confidence: 93%
“…Our results suggest that older women are more sensitive to muscle strength alterations throughout ageing, probably as a result of sex differences in muscle mass as well as hormonal factors [25, 26]. It seems to be particularly important for the weakest to enhance their levels of muscular strength and build up muscle mass early in life, where targeted preventative efforts may be launched, to reduce their risk of premature death.…”
Section: Discussionmentioning
confidence: 93%
“…It is well-known that serum total IGF concentrations are related with age and several indices of physiological ageing such as body composition, strength, mobility and mortality (14,16,18,27,28). However, the measurement of IGF1 by immunoassay does not take the modifying effect of the IGFBPs on IGF1 action into consideration and therefore we found it relevant to compare total IGF1 and bioactive IGF1 in healthy subjects.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, total IGF1 levels are associated with strength, mobility and mortality in women (18,19). The production of GH is three times higher in women compared with men, despite the fact that circulating IGF1 concentrations are only marginally higher in women (20)), which indicates a relative GH resistance in women.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand IGF-1 levels decrease during muscle atrophy (Frystyk, 2010;Goldspink et al, 2010). There is strong evidence to include IGF-1 in a set of blood-based biomarkers for the diagnosis of dynapenia and/or sarcopenia since several studies have shown that weak physical performance is associated with lower levels of circulating IGF-1 (Blain et al, 2012;Taekema et al, 2011).…”
Section: Introductionmentioning
confidence: 99%